1992
DOI: 10.2166/wst.1992.0060
|View full text |Cite
|
Sign up to set email alerts
|

Physiology of Geosmin Production by Anabaena circinalis Isolated from the Murrumbidgee River, Australia

Abstract: Chemical analysis and sensory assessment of river waters from the Murrumbidgee and Murray Rivers showed geosmin is an important odor compound. Experiments in culture using Anabaena circinalis isolated from the Murrumbidgee River, New South Wales, Australia showed that changes in chlorophyll per unit dry weight resulting from alterations in light intensity were paralleled by similar changes in geosmin/dry weight such that geosmin concentration was correlated with chlorophyll a over an extreme range of light con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
27
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 0 publications
7
27
0
Order By: Relevance
“…For example, this was observed in the Murrumbidgee River (Australia), where high geosmin levels were caused by the buoyancy-regulating cyanobacterium Anabaena circinalis (5), and in the Yodo River (Japan), where the stagnation of dammed river water promoted the growth of geosmin-producing Anabaena macrospora (28). Investigations of several other dammed rivers have shown elevated geosmin concentrations near to the dam (42), for example, in the Ruhr River (Westfalia, Germany), where this was most likely produced by the liberation of geosmin from microorganisms undergoing accelerated sedimentation in the stagnant waters beside the dam.…”
Section: Intra-and Extracellular Voc Fractionsmentioning
confidence: 98%
“…For example, this was observed in the Murrumbidgee River (Australia), where high geosmin levels were caused by the buoyancy-regulating cyanobacterium Anabaena circinalis (5), and in the Yodo River (Japan), where the stagnation of dammed river water promoted the growth of geosmin-producing Anabaena macrospora (28). Investigations of several other dammed rivers have shown elevated geosmin concentrations near to the dam (42), for example, in the Ruhr River (Westfalia, Germany), where this was most likely produced by the liberation of geosmin from microorganisms undergoing accelerated sedimentation in the stagnant waters beside the dam.…”
Section: Intra-and Extracellular Voc Fractionsmentioning
confidence: 98%
“…Wu and Jüttner (1988) found that the content of geosmin in cells varied with culture temperature. Bowmer et al (1992) showed that the geosmin/biomass values of Anabaena circinalis were negatively correlated to light intensities. Both Blevins et al (1995) and Saadoun et al (2001) suggested that increasing temperature repressed geosmin synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Taste/odour (T/O) problems are important for the drinking water industry, because consumers usually judge water quality by what they first perceive (Bowmer et al 1992;Ishida & Miyaji 1992). The origins of T/O problems in drinking water are often found in source water (Izaguirre et al 1999;Lin et al 2002).…”
Section: Introductionmentioning
confidence: 99%